Remote sensing of waste dumps in ecological safety management systems - Vambol, Sergiy; Vambol, Viola; Kondratenko, Olexandr; Suchikova, Yana (Lviv Politechnic Publishing House, 2017)
The paper describes an improved general model which is based on methods of remote scanning of Earth surface obtained by Space satellites with combination with GIS-technologies and methods of mathematical modeling. This model allows allocating and analyzing characteristics of carbon containing and organic components of places of accumulation of solid waste of domestic and industrial genesis of illegal waste dumps on Space images and also determining values of its area and dynamics of growth for monitoring of ecological safety level of urban systems.
Keywords: ecological safety; Earth remote scaning; waste dumps; space image; GIS-technologies